Teachers Professionalism and The Challenge Of Education In A Global Era - Sudrajat Sudrajat (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Abstract: The professional Attitude of a teacher is very necessary for the face of education in this global era. The task of the teacher is not only teaching but also educate, nurture, guide and shape the personality of the student. Mistakes teachers in understanding the profession will result in the shifting of the teacher function slowly. The relationship between teachers and students who need each other turns into a relationship of mutually indifferent, not blissful and boring. The professionalism of teachers is determined by behavior, will and capabilities on condition that Prime. Professionalisation should be viewed as a continuous process, so that the attitude and professional teachers actually formed in this process, pre-service education, educational upgrading, including in his coaching from professional organizations and the workplace, the society against the profession of teacher training, enforcement of the code of ethics of the profession, certification, improved quality of prospective teachers, rewards, etc collectively determine a person including professional development of teachers. This article presents an attempt discussion space for educators, prospective educators, and related parties in order to better understand, implement, and develop attitudes and behavior in the world of education through good example in mind, speech, and action.Keywords: Professional, Teacher, Education, Global Era